Re-evaluating Swedish membership in EMU: Evidence from an estimated model - Ulf Söderström (Sveriges Riksbank, 2008)
I revisit the potential costs and benefits for Sweden of joining the Economic and Monetary Union (EMU) of the European Union. I first show that the Swedish business cycle since the mid-1990s has been closely correlated with the Euro area economies, suggesting that common shocks have been an important driving force of business cycles in Europe. However, evidence from an estimated model of the Swedish economy instead suggests that country-specific shocks have been important for fluctuations in the Swedish economy since 1993, implying that EMU membership could be costly. The model also indicates that the exchange rate has to a large extent acted to destabilize, rather than stabilize, the Swedish economy, pointing to the costs of independent monetary policy with a flexible exchange rate. Finally, counterfactual simulations of the model suggest that Swedish inflation and GDP growth might have been slightly higher if Sweden had been a member of EMU since the launch in 1999, but also that GDP growth might have been more volatile. The evidence is therefore not conclusive about whether or not participation in the monetary union would be advantageous for Sweden.
Keywords: E42; E58; F41; 330; DSGE model; Monetary union; Open economy; Optimum Currency Area; Währungsunion; Eurozone; Wechselkurs; Zinsstruktur; Konjunktur; Volatilität; Wirtschaftswachstum; Mitgliedschaft; Schweden